Estrogen metabolites in a small cohort of patients with idiopathic pulmonary arterial hypertension. (1st March 2020) - Denver, Nina; Homer, Natalie Z.M.; Andrew, Ruth; Harvey, Katie Y.; Morrell, Nicholas; Austin, Eric D.; MacLean, Margaret R.
Abstract : Increased risk and severity of idiopathic pulmonary arterial hypertension (iPAH) is associated with elevated estradiol in men and postmenopausal women. Pulmonary arteries synthesise estradiol via aromatase and metabolise it via CYP1B1 to mitogenic metabolites; SNPs in aromatase and CYP1B1 have been associated with PAH. This suggests that estradiol metabolism could be altered in iPAH. This proof‐of‐concept study profiles estradiol and several metabolites of estradiol simultaneously in serum from iPAH patients and controls. We show that the estradiol and metabolite profile is altered in iPAH and that 16‐hydroxyestrone and 16‐hydroxyestradiol accumulate in iPAH patients with 16‐hydroxyestrone levels relating to disease severity.